Competence of Civil Servants in the Structure of Power Delegation of the Public Administration System - LOSHYTSKYI, Mykhailo V.; FRANTSUZ-YAKOVETS, Tetiana A.; KOVALCHUK, Andrii T.; KOVALCHUK, Trokhym T.; UVAROV, Volodymyr H. (Journal of Advanced Research in Law and Economics, 2019)
The powers by state authorities is primarily exercised using organizational, technological and legislative tools. Each public authority sets the goal of its activity to improve the quality of life of the population and optimize work of the state institutions system. In this regard, the relevance of the study is determined by the fact that the current model of power delegation is determined by the regulations, which are still based on command and administrative management methods. The novelty of the study is determined by the fact that the authors disclose the possibility of delegating power not only in the aspects of introducing an outsourcing system into the public administration sector, but also in the aspects of establishing a system for increasing the efficiency of government bodies in general and civil servants. The paper shows that the basis for increasing the effectiveness of the state management system in a country where the main idea is to increase the social well-being of society should be the opportunity to increase the competence of civil servants. The practical significance of the study is determined by the fact that the use of developments is possible in the structure of globalization of the public administration system. In this case, it is advisable to consider the possibility of stratification of international systems for assessing the competence of civil servants.